Kids speak: preferred parental behavior at youth sport events - Omli, J.; Wiese-Bjornstal, D. M. (Research Quarterly for Exercise and Sport, 2011)
News reports (e.g., Abrams, 2008) and scholarly research (e.g., Wiersma & Fifer, 2005) have indicated increasing concern that parent-spectator behavior at youth sport events may be problematic. Multiple strategies have been used to influence spectator behavior in youth sport contexts (e.g., "Silent Sundays"). However, it is unlikely that interventions aimed at changing parent-spectator behaviors have adequately considered young athletes' perspectives, because little is known about how children want parents to behave during youth sport events. Therefore, children (ages 7-14 years) were asked to describe how parents actually behaved at youth sport events and how they wanted parents to behave. Through grounded theory analysis (Charmaz, 2000), three parent "roles" emerged from the data—supportive parent, demanding coach, and crazed fan.